Fluid mechanics of environmental interfaces [electronic resource] - Gualtieri, Carlo; Mihailovic, Dragutin T. (Balkema-proceedings and monographs in engineering, water, and earth sciences, 2008)
Treats exchange processes occurring at the interfaces between atmosphere and the sea surface, and atmosphere and land surface - including the effect of vegetation, transport of dust and dispersion of